Beyond mere restriction: The bio-social mechanism of Sasi in fishery stock restoration within Maluku and Papua waters - Nurul Azmi (Journal of Earth Kingdom, 2026)
Background: The marine biodiversity crisis driven by overfishing in Eastern Indonesia has created mounting pressure for a structural transition in coastal governance one that moves away from centralized regulatory authority toward adaptive, locally embedded management regimes. The customary instrument of Sasi an oral indigenous prohibition regulating resource extraction consistently loses its coercive power when confronting external poachers who are not socially bound by local norms. Methods: This study examines the dynamics of legal hybridity in contemporary Sasi, evaluates multi-stakeholder collaboration using Common-Pool Resources (CPR) principles, and analyzes its impact on fishery stock restoration and social-ecological resilience in the waters of Maluku and Papua. Drawing on a socio-legal approach with a collective case study design, this research synthesizes secondary data from the 2015–2025 period, including village legal instruments such as village head decrees/surat keputusan kepala desa analyzed through thematic coding. Findings: Results indicate that integrating Sasi norms into Village Head Decrees functions as a systemic modifier, providing jurisdictional certainty and formal legal standing for customary wardens, and shifting enforcement from a moral-customary infraction to a legitimate village administrative violation. This governance synergy produces a triadic governance model that effectively coordinates customary, spiritual, and administrative authorities through low-cost collective monitoring. Biologically, the extraction pause during Sasi closure periods shows a consistent pattern of marine biomass recovery estimated at 60% for high-value species such as top shells (Trochus niloticus) and sea cucumbers (Holothuroidea). Conclusion: This study concludes that legal hybridity meaningfully strengthens coastal social-ecological resilience. Nonetheless, challenges persist regarding gender inclusivity disparities, horizontal boundary conflicts, and the risk of eroding local values through rigid bureaucratization. Novelty/Originality of this article: This study introduces the triadic governance model as a new conceptual framework that bridges the gap between informal indigenous norms and formal state administration in coastal management.